Blade [videorecording (DVD)] - Snipes, Wesley; Dorff, Stephen, 1973-; Kristofferson, Kris; Wright, N'Bushe, 1970- (New Line platinum series., 2001)
"Wesley Snipes stars as the tortured soul Blade -- half man, half immortal. Blade sharpens his lethal skills under the guidance of Whistler (Kris Kristofferson), his mentor, guardian, and fellow hunter of the night. When the bloodthirsty Immortals' lord, Deacon Frost (Stephen Dorff), declares war on the human race, Blade is humanity's last hope for survival." -- Container.